Peran Mahasiswa KPPM dalam Mengatasi Kenakalan Remaja melalui Sekolah & Desa - Roni Parapat; Ifka Siregar; Nico Barus; Dekson Pardosi; Geme Situngkir (Lembaga Pengembangan Kinerja Dosen, 2025)
Lack of parental supervision due to busyness in the agricultural sector and other jobs is one of the main factors in the increase in juvenile delinquency in Patane II Village and SMA N 1 Parmaksian. The lack of supervision and guidance makes children and adolescents more vulnerable to negative behavior. KPPM students took the initiative to carry out activities with children and socialize about juvenile delinquency, both at school and in the village environment, in order to increase awareness and provide education to adolescents about the negative impacts of deviant behavior. The purpose of this study was to identify the factors causing juvenile delinquency in Patane II Village and also propose solutions to overcome the problem. This study used a qualitative descriptive method by conducting observations, interviews, and documentation to understand the types of juvenile delinquency, the factors causing it, and efforts to overcome it through activities and socialization. Based on the results of the study, the activities and socialization can help children understand and increase their concern for their living environment in Patane II Village and SMA N 1 Parmaksian and encourage them to take positive actions. Therefore, handling juvenile delinquency requires comprehensive planning that involves the community, school, and family to create an environment that supports healthy adolescent development.